2019
DOI: 10.5606/tgkdc.dergisi.2019.17972
|View full text |Cite
|
Sign up to set email alerts
|

Complications and management strategies of totally implantable venous access port insertion through percutaneous subclavian vein

Abstract: Bu çalışmada perkütan subklaviyen ven yoluyla tamamen implante edilebilir venöz erişim portu yerleştirilen hastaların klinik özellikleri, periprosedürel sonuçları, erken ve geç komplikasyonları ve tedavi stratejileri sunuldu.Ça lış mapla nı:Mart 2012 -Haziran 2018 tarihleri arasında perkütan landmark yöntemi ile subklaviyen ven yoluyla 2000 kanser hastasına (1066 erkek, 934 kadın; ort. yaş: 58.4±12.7 yıl; dağılım, 18-88 yıl) toplam 2084 port cihazı yerleştirildi. Demografik özellikler, primer tanı, teknik başa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 35 publications
0
22
0
Order By: Relevance
“…Previous long-term observations studies had reported that the complication-related removal rate accounted or between 1% and 8.3%. [ 15 , 22 , 23 ] The reasons for removal or repositioning of TIVAPs are summarized in Table 3.…”
Section: Discussionmentioning
confidence: 99%
“…Previous long-term observations studies had reported that the complication-related removal rate accounted or between 1% and 8.3%. [ 15 , 22 , 23 ] The reasons for removal or repositioning of TIVAPs are summarized in Table 3.…”
Section: Discussionmentioning
confidence: 99%
“…One study analyzed 9346 patients who received TIAP from 2007 to 2016; of the 79 patients who underwent catheterization from the left side, the catheter tip strayed into AV in 7 (0.7%), while the incidence of left catheterization was 8.9% 5 . In 2084 operations involving catheterization via SV, catheter malpositioning was the second most common early complication 6 . A total of 350 TIAP insertions were performed in our inpatient department from January 2019 to June 2019, of which 25 cases (8.0%) involved left vascular access; the catheter migrated to AV in 1 case and to ITV in another, for a total incidence rate of 0.5%.…”
Section: Discussionmentioning
confidence: 99%
“…5 In 2084 operations involving catheterization via SV, catheter malpositioning was the second most common early complication. 6 A total of 350 TIAP insertions were performed in our inpatient department from January 2019 to June 2019, of which 25 cases (8.0%) involved left vascular access; the catheter migrated to AV in 1 case and to ITV in another, for a total incidence rate of 0.5%. The 2 types of allotopia (immediate or postoperative spontaneous) differ in their causes.…”
Section: Discussionmentioning
confidence: 99%
“…Major issues related to intravenous port implantation include first attempt success rate [ 1 , 2 , 3 ] and peri-operative and late complications [ 4 , 5 , 6 , 7 ]. Several native vessels can be used as the entry vessel for chest port insertion, including the cephalic vein [ 2 , 3 ], deltoid branch of the thoracoacromial vein [ 8 ], the axillary vein [ 1 , 9 ], the internal jugular vein [ 3 ], the external jugular vein [ 2 ], the left brachiocephalic vein [ 10 , 11 ], and the subclavian vein [ 12 , 13 , 14 ]. However, different implantation methods are used for different target vessels and varying long-term results have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Third, completely avoid subclavian vein and lower neck IJV puncture. This eliminates iatrogenic arterial puncture [ 13 , 14 ], hemothorax [ 17 ], and mediastinal hematoma [ 18 ]. In addition, pneumothorax [ 13 , 14 ] and catheter fracture related to pinch-off syndrome [ 19 ] are completely avoided.…”
Section: Introductionmentioning
confidence: 99%